2016
DOI: 10.1111/1758-2229.12438
|View full text |Cite
|
Sign up to set email alerts
|

Fungal identification biases in microbiome projects

Abstract: Fungi are the key players in ecosystems as well as in plant and human health. High-throughput molecular identification of fungi has greatly progressed our understanding about the diversity of mutualists, saprotrophs, and pathogens. We argue that the methods promoted by the microbiome consortia are suboptimal for detection of the most important fungal pathogens and ecologically important degraders. We recommend several sets of optimized primers for analysis of fungi or all eukaryote groups based on either short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(150 citation statements)
references
References 39 publications
2
145
0
3
Order By: Relevance
“…Alternatively, we opted to compare the taxonomic diversity as far as possible and to comment on the differential detection of taxa. Our approach, which considers the lichen thallus as distinctive and still largely unexplored niche for unknown fungal assemblages, further strengthens the perception that diversity estimates based on metabarcoding are limited by the barcode locus selected (Tedersoo et al 2015; Tedersoo and Lindahl 2016). …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Alternatively, we opted to compare the taxonomic diversity as far as possible and to comment on the differential detection of taxa. Our approach, which considers the lichen thallus as distinctive and still largely unexplored niche for unknown fungal assemblages, further strengthens the perception that diversity estimates based on metabarcoding are limited by the barcode locus selected (Tedersoo et al 2015; Tedersoo and Lindahl 2016). …”
Section: Discussionsupporting
confidence: 66%
“…They have been carried out on both Ascomycota (Nilsson et al 2009; Bellemain et al 2013) and Basidiomycota (Badotti et al 2017). Taxonomic bias can be introduced by the choice of primers, as these cause a higher number of mismatches in different taxa (Bellemain et al 2013; Tedersoo et al 2015; Tedersoo and Lindahl 2016). Some studies also reported that the two spacers are prone to preferential amplification at different levels (Nilsson et al 2009; Mello et al 2011; Bellemain et al 2013; Bazzicalupo et al 2013; Monard et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these results indicate that the ITS2 subregion shows either more than two‐fold better resolution for OTU separation at the 97% similarity threshold or accommodates more spurious OTUs. Previously, we attributed the greater richness of ITS2 fungal OTUs to lower primer bias (Tedersoo et al ., ,b; Tedersoo & Lindahl, ), which is minimized here by the use of degenerate ITS2 primer variants (see below). Other studies have observed comparable richness profiles for ITS1 and ITS2 subregions (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Of the forward primers, the universal 1389F primer performed best by amplifying all fungal phyla and various groups of non‐fungal eukaryotes that contributed 16% of all sequences on average. The ITS9MUNngs primer (5′‐TACACACCGCCCGTCG‐3′; Tedersoo & Lindahl, ) 2 bp downstream has a terminal mismatch to Archaea and Bacteria, but similar affinity to eukaryotes, and can be used alternatively.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, our results contribute to the evidence that fungal primers for the ITS rDNA, which is the preferred fungal barcode (Lindahl et al ., ), fail to provide proper coverage of AMF diversity, as they do for other important fungal groups (Bellemain et al ., ; Ihrmark et al ., ; Tedersoo and Lindahl, ). Nonetheless, the specific ITS2 primer pair we used in this case study can provide enough data to estimate community structure without major biases and to make reliable conclusions on AMF relation to environmental variables.…”
Section: Discussionmentioning
confidence: 99%